Standardization in the scientific communication context (Perspectivas em Ciência da Informação, 2007)
Since the 70s standardization is pointed as a significant factor in scientific communication. In several fields, studies indicated the importance of formal aspects for the acceptation or rejection of papers for publication, which increases the scientific communication standardization value. Considering that the university have to improve the scientific communication, this paper presents a discussion under this issue.